Part II. Common questions and misconceptions about creatine supplementation: what does the scientific evidence really show? - Jose Antonio; Ann F. Brown; Darren G. Candow; Philip D. Chilibeck; Stacey J. Ellery; Scott C. Forbes; Bruno Gualano; Andrew R. Jagim; Chad Kerksick; Richard B. Kreider; Sergej M. Ostojic; Eric S. Rawson; et al. (Journal of the International Society of Sports Nutrition)
Creatine monohydrate supplementation (CrM) is a safe and effective intervention for improving certain aspects of sport, exercise performance, and health across the lifespan. Despite its evidence-based pedigree, several questions and misconceptions about CrM remain. To initially address some of these concerns, our group published a narrative review in 2021 discussing the scientific evidence as to whether CrM leads to water retention and fat accumulation, is a steroid, causes hair loss, dehydration or muscle cramping, adversely affects renal and liver function, and if CrM is safe and/or effective for children, adolescents, biological females, and older adults. As a follow-up, the purpose of this paper is to evaluate additional questions and misconceptions about CrM. These include but are not limited to: 1. Can CrM provide muscle benefits without exercise? 2. Does the timing of CrM really matter? 3. Does the addition of other compounds with CrM enhance its effectiveness? 4. Does CrM and caffeine oppose each other? 5. Does CrM increase the rates of muscle protein synthesis or breakdown? 6. Is CrM an anti-inflammatory intervention? 7. Can CrM increase recovery following injury, surgery, and/or immobilization? 8. Does CrM cause cancer? 9. Will CrM increase urine production? 10. Does CrM influence blood pressure? 11. Is CrM safe to consume during pregnancy? 12. Does CrM enhance performance in adolescents? 13. Does CrM adversely affect male fertility? 14. Does the brain require a higher dose of CrM than skeletal muscle? 15. Can CrM attenuate symptoms of sleep deprivation? 16. Will CrM reduce the severity of and/or improve recovery from traumatic brain injury? Similar to our 2021 paper, an international team of creatine research experts was formed to perform a narrative review of the literature regarding CrM to formulate evidence-based responses to the aforementioned misconceptions involving CrM.